Hypothermic machine perfusion in liver transplantation. Issue 3 (June 2016) - Schlegel, Andrea; Kron, Philipp; Dutkowski, Philipp
Abstract : Purpose of the review: The purpose of the review is to report recent human application of hypothermic machine liver perfusion, and to discuss potential protective mechanisms. Recent findings: Human application of hypothermic machine liver perfusion is still very limited. Currently, three transplant centers apply this novel treatment in donation after cardiac death (DCD) or donation after brain death (DBD) liver grafts. In all cases, endischemic perfusion was performed after initial cold storage for organ transport. Perfusion conditions differ slightly in terms of oxygenation (pO2 15–60 kPa), perfusion route (dual vs. portal), perfusion time (2–4 h), and perfusate. Summary: The current data support the hypothesis that applying endischemic hypothermic machine liver perfusion protects extended criteria DBD and DCD livers from initial reperfusion injury, with better graft function and less biliary complications. Hypothermic machine perfusion may therefore offer revitalization of liver grafts before implantation by a simple and practical perfusion technique with a high impact on enlarging the donor pool. Multicentric phase III randomized control trials in DBD and DCD liver transplantation have been initiated to further test this strategy, which may establish machine liver perfusion in the clinical setting.